RANCANG BANGUNG APLIKASI ENKRIPSI DENGAN MENGGUNAKAN METODE RSA BERBASIS WEB - Ricky Maulana Fajri (UNIVERSITAS INDO GLOBAL MANDIRI)
The use of the internet has boost up the interaction of the data and information. The internet has made the transfer of information become faster and reliable. However, there are many malicious applications which consider would violate the information. Therefore, there is a need for a network security to make sure the security on the internet. Network security has three main goals, namely confidentiality, integrity and availability. There are several techniques of an encryption, they are symmetric and asymmetric encryption. In symmetric encryption the key used to encrypt and decrypt a message is similar, while the key used in asymmetric encryption is different. There are many encryption types which are used in today life for example DES (Data encryption Standard), Triple DES and RSA. In this paper an application of encryption will be created. It will be created using PHP programming language and several stages of encryption for instance calculating the hash value using SHA-1, encrypt Hash value using RSA. Finally, the decryption process will be explored to make the encrypted message readable to the user.Keyword: Encryption, RSA, SHA-, Hash.